2007
DOI: 10.1002/aoc.1205
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and cytotoxicity evaluation of new cerium(III), lanthanum(III) and neodymium(III) complexes

Abstract: Complexes of cerium(III), lanthanum(III) and neodymium(III

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Given that the ligands used are well-known biologically active compounds, we compared them with the lanthanide(III) complexes which we have characterized. [22][23][24][25][26]28,29 Detailed analysis of AOA and Ln(III)-AOA systems revealed that the binding mode in the complexes was bidentate through the carboxylic oxygen atoms. It has been suggested that CCA binds to Ln(III) ions through both oxygen atoms of the carboxylic and carbonylic groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the ligands used are well-known biologically active compounds, we compared them with the lanthanide(III) complexes which we have characterized. [22][23][24][25][26]28,29 Detailed analysis of AOA and Ln(III)-AOA systems revealed that the binding mode in the complexes was bidentate through the carboxylic oxygen atoms. It has been suggested that CCA binds to Ln(III) ions through both oxygen atoms of the carboxylic and carbonylic groups.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the lanthanide(III) complexes of AOA and CCA as well as their theoretical, analytical, spectral, and structural characterization have been previously reported by us. [22][23][24][25][26]28,29 Shortly: the compounds used for preparing the solutions were Merck products, p.a. grade:…”
Section: Complexesmentioning
confidence: 99%
“…Coumarins are an important group of organic compounds that show a wide variety of biological activity as antitumour and antiproliferative effects. [7][8][9][10] Complexes of rare earth metal as cerium(III), lanthanum(III) and neodymium(III), having coumarines as ligand, were examined on different cell lines. [11] Rogers and coworkers reported the cytotoxic activity of acenocumarol samarium(III) and gadolinium(III) complexes against melanoma B16 and fibrosarcoma L929 cell lines.…”
Section: Introductionmentioning
confidence: 99%